Pengaruh Pola Asuh Orang Tua Terhadap Perkembangan Sosial Emosional Anak Usia 5-6 Tahun di Gugus I Kecamatan Sekarbela Tahun 2021 - Januari Nurfitri; I Nyoman Suarta; Ika Rachmayani (Indonesian Journal of Elementary and Childhood Education, 2022)
The reason behind this research is because they want to know directly the influence of parenting styles on the social emotional development of children aged 5-6 years in Cluster I, Sekarbela District in 2021. This research aims to determine the effect of parenting styles on children's social emotional development. aged 5-6 years in Cluster I of Sekarbela District in 2021. This research is a quantitative study using an ex post facto approach. The population in this study were children aged 5-6 years in Cluster I of Sekarbela District which consisted of 3 schools belonging to Group I, while the sample in this study were 30 parents and 30 children aged 5-6 years. The results of the calculation of the hypothesis test found that the sig. = 0.596 and a = 0.05. Then Ho is accepted and Ha is rejected, so the data is not significant or cannot be applied to the population where the sample is taken. It can be concluded that there is no effect of parenting style on the social emotional development of children aged 5-6 years in Cluster I Sekarbela District in 2021. Parents need to ask teachers more about how their children are developing at school and pay attention to whether the actions taken by parents is correct or not.